Tracheocutaneous fistula ‐ A surgical challenge - Chirakkal, Pramod (Clin Case Rep, 2021)
Tracheocutaneous fistula presents a challenge to the surgeon as different factors affect its formation and healing. A multidisciplinary approach and proper patient counseling, duration of cannulation, and comorbidities help in prognosis and outcome.